The Impact of Tax Avoidance on Audit Report Lag with Audit Fee as a Moderating Variable - Soeparjono, Permata Indhira Hajj; Senjani, Yayu Putri (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
Purpose: This research examines the influence of tax avoidance measured through ETR and CETR on audit report lag, with audit costs as a moderating variable. The research is updated by integrating audit costs as a moderating variable. Methodology: It is quantitative research employing secondary data from annual reports. The selection of companies is based on predefined criteria using a purposive sampling method, resulting in a sample of 140 observations. The research is tested using panel data regression analysis with Stata 14 software. Findings: Based on the data analysis results, it can be concluded that (1) tax avoidance, measured through both ETR and CETR, has a significant positive impact on audit report lag, and (2) audit fee as a moderating variable weakens the positive relationship between tax avoidance, either ETR or CETR, and audit report lag. Novelty: The study is conducted on companies listed on the Indonesia Stock Exchange, categorized into four stock sectors with audit report lag from 2018 to 2022.